Impacto da reconstrução imediata da mama em tempo único na postura corporal de pacientes com câncer de mama - Chichof, Gustavo Tiago (2012)
The aim of this study is to detect, evaluate and compare quantitatively possible local pain and postural changes resulting from the immediate breast reconstruction in a single step, ie, with the contralateral breast symmetrization concomitant. This is a prospective study in which 19 women underwent surgical treatment of breast cancer with immediate reconstruction technique. Were divided into two groups, with reconstruction of mastectomy shown (n = 12) and the group quadrantectomy with immediate reconstruction (n = 07). All patients were examined before surgery and after 1 month follow-up evaluations in the 2nd, 3rd, 4th and 5th month postoperatively. To determine body posture and their possible changes in the postoperative period, we used variables that show changes in body posture, which are the projection of the head, protrusion of the shoulders, abduction of the scapula, asymmetry of the shoulders, lateral inclination of the column, chest curve, lumbar curve, center of gravity and angle of the breasts, these parameters being obtained in the sagittal and coronal planes from the method of computerized photogrammetry. Changes were noted in relation to previous body symmetry in the variables, abduction of the scapula, asymmetry of the shoulders, lateral inclination of the column, center of gravity and angle of the breasts. The surgical procedure for treatment of breast cancer with immediate reconstruction technique for generating single time did not show statistically significant negative interference on the postural pattern of the patient groups compared to preoperative values. Statistically significant differences (ANOVA, p <0.05) between groups of mastectomy and quadrantectomy in breast angle variable and lumbar curvature, the angle of the breasts increased in the postoperative group mastectomy with immediate reconstruction and single-time curvature lumbar differ between the groups preoperatively, with a decrease in curvature similar postoperative evaluations of both groups. The average pain was presented by the groups characterized mildly according to visual analog scale.